The measurement of Physical Workload and Mental Workload Level of Medical Personnel - Restuputri, Dian Palupi; Pangesti, Anindia Karunia; Garside, Annisa Kesy (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
As the primary health reference center, a hospital is required to provide excellent quality services to each patient. The impact of the extreme physical and mental workload cause negligence in activities. It affects the quality of services provided by medical personnel. This study investigated the level of mental workload and physical workload in medical staff in a hospital. This study was conducted at 15 units in the hospital. The mental workload was assessed using the NASA-TLX Questionnaire. The physical workload analysis was carried out with the Heart Rate reserve percentage of medical personnel. The results of this study show that the mental workload on nurses in the ICU is higher than the other units. Whereas the calculation of physical load using% HR reserve turns out the head of the nurse in-unit class 1 has the highest value compared to the others unit. The statistical analysis showed there was a difference in the general practitioner workload toward the Head of the Nursing.